Analisis Kesalahan Berbahasa Bentuk Baku Pada Masyarakat Poleang Barat - Hamrin Hamrin (Publikasi Indonesia, 2022)
conversmost of the errors that appear in a piece of writing or spoken speech are caused by the presence of language spelling problems, errors in interpretation, the use of non-standard words that do not match their function. The purpose of studying language learners' language errors is to identify elements of the target language that cause language learning difficulties and to find explanations about the causes of language difficulties that result in language errors. The method used to identify language errors in the West Poleang community is a qualitative descriptive method with a note-taking technique. Ation Spoken language errors made by language users include errors at the phonological, morphological, syntactic, and semantic levels. Mistakes made unconsciously due to lack of understanding of the phoneme structure and morphemes of the language being used.